Hypothalamic tanycytes—masters and servants of metabolic, neuroendocrine, and neurogenic functions - Goodman, Timothy; Hajihosseini, Mohammad K. (Frontiers in Neuroscience, 2015)
There is a resurgent interest in tanycytes, a radial glial-like cell population occupying the floor and ventro-lateral walls of the third ventricle (3V). Tanycytes reside in close proximity to hypothalamic neuronal nuclei that regulate appetite and energy expenditure, with a subset sending projection into these nuclei. Moreover, tanycytes are exposed to 3V cerebrospinal fluid and have privileged access to plasma metabolites and hormones, through fenestrated capillaries. Indeed, some tanycytes act as conduits for trafficking of these molecules into the brain parenchyma. Tanycytes can also act as neural stem/ progenitor cells, supplying the postnatal and adult hypothalamus with new neurons. Collectively, these findings suggest that tanycytes regulate and integrate important trophic and metabolic processes and possibly endow functional malleability to neuronal circuits of the hypothalamus. Hence, manipulation of tanycyte biology could provide a valuable tool for modulating hypothalamic functions such as energy uptake and expenditure in order to tackle prevalent eating disorders such as obesity and anorexia.